The Role of HIF-1α in Atrial Fibrillation: Recent Advances and Therapeutic Potentials - Feng Zhou; Jia-Bin Zhou; Tian-Peng Wei; Dan Wu; Ru-Xing Wang (Reviews in Cardiovascular Medicine)
The steady increase in life expectancy throughout the world is contributing to an increased incidence of atrial fibrillation (AF), which imposes a significant socioeconomic toll on affected patients and societies. The mechanisms underlying atrial fibrillation are multifaceted and vary among individuals. Hypoxia is a process that is closely linked to AF onset and progression. Hypoxia-inducible factor 1-alpha (HIF-1α) is a transcription factor that serves as a key regulator of oxygen homeostasis within cells through its activation under hypoxic conditions and subsequently coordinates various pathophysiological responses. High levels of HIF-1α expression are evident in AF patients, and facilitate the progression from persistent AF to permanent AF. Thus, HIF-1α may serve as a promising target for novel therapeutic strategies aimed at the prevention and treatment of AF. This review provides an overview and synthesis of recent studies probing the relationship between HIF-1α and AF, providing a foundation for future studies and the development targeted drug therapies.